High-throughput evaluation of half-metallicity of Co2MnSi Heusler alloys using composition-spread films and spin-integrated hard X-ray photoelectron spectroscopy - Ryo Toyama; Shunsuke Tsuda; Yuma Iwasaki; Thang Dinh Phan; Susumu Yamamoto; Hiroyuki Yamane; Koichiro Yaji; Yuya Sakuraba (Science and Technology of Advanced Materials)
We demonstrate high-throughput evaluation of the half-metallicity of Co2MnSi Heusler alloys by spin-integrated hard X-ray photoelectron spectroscopy (HAXPES) of composition-spread films performed with high-brilliance synchrotron radiation at NanoTerasu, which identifies the optimum composition showing the best half-metallicity. Co75–xMnxSi25 composition-spread thin films for x = 10–40% with a thickness of 30 nm are fabricated on MgO(100) substrates using combinatorial sputtering technique. The L21-ordering and (001)-oriented epitaxial growth of Co2MnSi are confirmed by X-ray diffraction for x = 18–40%. The valence band HAXPES spectra exhibit a systematic compositional dependence and the smallest photoemission intensity at the Fermi level (EF) for a slightly Mn-rich composition of x = 27%. The density of states (DOS) for L21-ordered Co2MnSi with different Mn compositions obtained from first-principles calculation also show the smallest total DOS at EF for x = 27% because of the formation of a clear half-metallic gap in the minority spin channel and the less localized d-states in the majority spin channel, indicating the best half-metallic nature of this composition. Our experimental results demonstrate that high-throughput evaluation of half-metallicity is possible even with spin-integrated HAXPES by capturing systematic changes in the electronic structures through the measurements on the composition-spread film. Moreover, the anisotropic magnetoresistance (AMR) of the composition-spread film is measured for electric current directions along the [110] and [100] of Co2MnSi. Previous studies indicated that a larger negative AMR ratio is a signature of a higher spin polarization. The largest negative AMR ratio is observed for x = 27% for both current directions, which also supports the best half-metallicity for this off-stoichiometric composition.